Problematika Penegakan Hukum di Indonesia : Antara Kepastian Hukum, Keadilan, dan Kepentingan Politik - Virginia Usfunan; Yudith Bana; Efatha F.B. Duarte (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Indonesia constitutionally positions itself as a state based on law (rechtsstaat), yet the practice of law enforcement continues to face a persistent problem, namely how to reconcile legal certainty, justice, and political interest that frequently intersect within the judicial process. This article examines the tension among these three values in the context of Indonesian law enforcement practices, particularly the tendency of formalistic-procedural approaches to override substantive justice, as well as the recurring pattern of political influence shaping the direction of legal cases. Using a normative juridical method with statutory, conceptual, and case approaches, this study analyzes secondary legal materials, including statutory regulations, court decisions, and relevant legal literature. The findings indicate that the dominance of legal positivism, weak law enforcement institutions, and the proximity between legal and political elites have produced disparities in the application of law between ordinary citizens and parties holding social, economic, or political power. This article argues that harmonizing legal certainty, justice, and independence from political interference requires strengthening the institutional independence of law enforcement bodies, reforming the legal culture of officials, and reinforcing public oversight as an inseparable part of Indonesia's ongoing legal reform agenda. Keywords: law enforcement; legal certainty; justice; political interest; Indonesia Abstrak Indonesia secara konstitusional menempatkan dirinya sebagai negara hukum (rechtsstaat), namun praktik penegakan hukum masih dihadapkan pada persoalan mendasar, yaitu bagaimana mendudukkan kepastian hukum, keadilan, dan kepentingan politik yang kerap saling bersinggungan dalam proses peradilan. Artikel ini mengkaji ketegangan di antara ketiga nilai tersebut dalam konteks praktik penegakan hukum di Indonesia, khususnya kecenderungan pendekatan formalistis-prosedural yang mengesampingkan keadilan substantif, serta pola berulang pengaruh politik yang turut membentuk arah penanganan perkara hukum. Dengan menggunakan metode yuridis normatif melalui pendekatan perundang-undangan, pendekatan konseptual, dan pendekatan kasus, penelitian ini menganalisis bahan hukum sekunder berupa peraturan perundang-undangan, putusan pengadilan, dan literatur hukum yang relevan. Hasil kajian menunjukkan bahwa dominasi positivisme hukum, lemahnya kelembagaan penegak hukum, serta kedekatan antara elite hukum dan elite politik telah menciptakan disparitas penerapan hukum antara masyarakat biasa dan pihak yang memiliki kekuasaan sosial, ekonomi, maupun politik. Artikel ini berargumen bahwa harmonisasi kepastian hukum, keadilan, dan independensi dari intervensi politik memerlukan penguatan independensi kelembagaan penegak hukum, reformasi budaya hukum aparat, serta penguatan mekanisme pengawasan publik sebagai bagian tidak terpisahkan dari agenda reformasi hukum di Indonesia. Kata Kunci: penegakan hukum; kepastian hukum; keadilan; kepentingan politik; Indonesia